1956
DOI: 10.1113/expphysiol.1956.sp001212
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption of Bicarbonate‐saline Solutions by the Small Intestine and Colon of the White Rat

Abstract: 1. During the absorption of isotonic solutions containing 160 mM Na, 135 mM Cl and 25 mM HCO3, the contents of rat jejunum become progressively more acid than the contents of the ileum or colon. 2. During absorption there is a net entry of total CO2 into the contents of the ileum and colon, while from the jejunum there is a net absorption of total CO2. 3. The carbonic anhydrase inhibitor 6063 depresses the absorption of water and electrolytes from the jejunum, ileum and colon, and reverses the direction of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

1957
1957
1991
1991

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 4 publications
3
75
0
Order By: Relevance
“…The secretion of bicarbonate ions by the colon has been demonstrated in several species (Parsons, Powell & Pyrah, 1952;D'Agostino, Leadbetter & Schwartz, 1953;Parsons, 1956) and some evidence for active transport of the ion was produced by Cooperstein & Brockman (1958). The present experiments did not allow assessment of the latter possibility but did demonstrate that none of the variations produced by Na depletion affected the secretion rate.…”
Section: Ionic Fluxesmentioning
confidence: 35%
“…The secretion of bicarbonate ions by the colon has been demonstrated in several species (Parsons, Powell & Pyrah, 1952;D'Agostino, Leadbetter & Schwartz, 1953;Parsons, 1956) and some evidence for active transport of the ion was produced by Cooperstein & Brockman (1958). The present experiments did not allow assessment of the latter possibility but did demonstrate that none of the variations produced by Na depletion affected the secretion rate.…”
Section: Ionic Fluxesmentioning
confidence: 35%
“…Parsons [1956] has suggested that part of the sodium absorption in the intestine may take place through a sodium-hydrogen ionic exchange, and it might be surmised that such a process would be inhibited by increasing the H+ concentration. A comparable finding in the case of sodium is that of Schoffeniels [1955], who has shown clearly that both the influx and net transport of Na ions across frog skin are dependent upon the pH of the bathing solution on either side, both the net transport and the inward flux being reduced in the presence of increasing H-ion concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been pointed out that the regions of the lateral interspaces below the tight junctions are unlikely to represent the locus of discriminatory permeability properties [10], and it seems reasonable to assume that the permeability ratio appropriate to the basal regions of the lateral interspace is unity. It has been shown that the pattern of acid base metabolism in rat jejunum includes secretion of hydrogen ions to the mucosal side and movement of metabolic anions, such as lactate and bicarbonate, into the serosal fluid [16,30]. Since the metabolic anions are not accompanied by hydrogen ions their movements may be expected to increase the pH in the lateral interspace, and it can be seen that this space can be suggested to have permeability properties and a pH value that are qualitatively appropriate to the intermediate compartment of a three-compartment system that performs net transport of weak acids towards the serosal side and of weak bases in the opposite direction.…”
Section: Three-compartment System For Weak Electrolyte Transportmentioning
confidence: 99%